Peran Mediasi Present bias dan Mental accounting pada Pengaruh Adopsi Buy Now Pay Later (BNPL) terhadap Keputusan Pembelian Gen Z - Faiz Alamsyah; Muhammad Hamdi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to examine the effect of Buy Now Pay Later (BNPL) usage on Gen Z’s Keputusan Pembelians by incorporating present bias and mental accounting as mediating variables. A quantitative research design was employed using a survey method involving 169 Gen Z respondents, aged 18–28 years, who had used BNPL services at least once within the last six months, thereby representing active BNPL users among Gen Z. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Hypothesis testing and mediation effects were assessed using the bootstrapping procedure, which applies resampling techniques to generate robust estimates of path coefficients, t-statistics, and p-values. The results indicate that BNPL adoption has a positive and significant effect on Keputusan Pembelians. Furthermore, mediation analysis confirms that present bias and mental accounting significantly mediate the relationship between BNPL adoption and Keputusan Pembelians, suggesting that consumer psychological mechanisms play a crucial role in amplifying the impact of BNPL on Gen Z’s purchasing behavior. These findings contribute theoretically to the development of behavioral economics by elucidating the role of cognitive biases in digital financial services. Practically, the results provide insights for FinTech companies and regulators in the digital financial sector to design marketing strategies and consumer protection policies that promote more responsible BNPL usage.